Seasonal changes of mineral nutrient absorption and allocation in the branch and leaf of Zanthoxylum bungeanum ‘Hanyuan’ during the fruit development - Lu, Shuaijie; Xv, Jing; Gong, Yuanjia; Gong, Wei; Hui, Wenkai; Qiu, Jing; Zhai, Yafang; Wang, Jingyan (Frontiers in Plant Science, 2024)
The dynamic changes of mineral nutrients in the leaf and branch of Zanthoxylum bungeanum ‘Hanyuan’ during fruit development can serve as a basis for nutrient diagnosis and scientific fertilization. The content of Nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) in the branch and leaf were measured using current-year shoots of 10-year-old Z. bungeanum ‘Hanyuan’ during the fruit development period, and the corresponding nutrient content in soil of the orchard were also determined to explore the nutrient demand patterns of Z. bungeanum ‘Hanyuan’ trees. Both branch and leaf exhibited relatively high levels of various nutrients during the early stages of fruit growth, then declined temporarily. At fruit maturity, the content of Ca and K in branches was the highest, while the content of Ca and N in leaves was the highest. At fruit maturity, the average nutrient content of N, P, K, Ca, Mg, Fe, Mn, Cu, and Zn in the branches and leaves were 17.25 g/kg, 1.99 g/kg, 18.84 g/kg, 26.14 g/kg, 3.69 g/kg, 215.61 mg/kg, 248.85 mg/kg, 13.08 mg/kg, and 53.77 mg/kg. The N, K, Ca, Fe, Cu, and Zn content in the branches and leaves significantly correlated with those nutrients content in the soil. The appropriate period for nutrient diagnosis of Z. bungeanum is 39−86 d after flowering (AF), with the critical period for branch and leaf nutrient requirements being 1−39 d AF. This provides a basis for nutrient supplements in Z. bungeanum ‘Hanyuan’ orchards management.